ANALISIS KONDISI KERUSAKAN JALAN KABUPATEN PASURUAN MENGGUNAKAN METODE BINA MARGA (Studi Kasus : Jl Ahmad Yani – Jl. Dr. Soetomo) - Eva Sundari; Nurin Izzah Rahmawati (Universitas Trisakti, 2022)
The Tengger Mountains Complex, which includes Mount Bromo, is the primary tourist attraction in the Pasuruan Regency. As a consequence, there has been an increase in the volume of traffic from one year to the next, particularly on the section of road that connects Ahmad Yani and Doctor Soetomo, which has led to a decline in the quality of the road. The objectives of the research will be to: 1) Determine the typical daily traffic levels and class scores along a number of different portions located within the Pasuruan area. 2) To assess the nature of the destruction that was sustained by the road that is the subject of this investigation. 3) To determine the significance of the state of the route that is being studied. This research makes use of a road final inspection calculated using the Bina Marga method. The survey data collected for this study includes both LHR and road damage data. According to the results of the study conducted on Jalan Ahmad Yani and Jalan Dokter Soetomo, the LHR class value for this location is 4, and the LHR value is 1234 pcu/hour. In the meantime, the alligator crack, that has surface area of 376.96 m2 and a significance order value of 8, is the most prevalent type of destruction along the road.